IATROGENIC EVENTS OF ORAL ANTITHROMBOTIC THERAPY. BETWEEN SCYLLA AND CHARYBDIS - L. I. Dvoretsky; V. V. Rezvan; A. V. Magnitsky (Архивъ внутренней медицины, 2016)
Thrombotic complications are a common problem in clinical practice. The most important are coronary thrombosis with myocardial infarction, ischemic cerebral infarcts in patients with atrial fibrillation, venous thrombosis complicated by pulmonary embolism. The use of oral antiplatelet therapy significantly reduced the incidence of fatal thrombotic complications. However, use of this group of drugs is associated with an increased risk of bleeding, which often turn out to be fatal for the patient. In the article presented the modern tactics of treatment of patients receiving a variety of oral antithrombotic agents, described a typical example of clinical complications.